2017
DOI: 10.1186/s40001-017-0272-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimized protocol for whole organ decellularization

Abstract: BackgroundThe idea of tissue decellularization to gain matrices for tissue engineering is promising. The aim of the present study is to establish a safe and reproducible protocol for solid tissue decellularization that prevents the architecture of the matrix with the inherent vascular network.MethodsThe study was performed in rat kidneys which were decellularized by a SDS-based perfusion protocol. Perfusion time and SDS concentration were systematically changed to obtain the shortest and most gentle protocol t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…SDS is typically more effective for removing cell residues from tissue compared to other detergents but is also more disruptive to ECM in higher concentrations and exposure time [32]. Thorough residual chemicals removal from ECM after decellularization, particularly detergents such as SDS is important as cytotoxicity is possible and will inhibit or completely negate the beneficial properties of a cell-free ECM scaffold [32,33] Our results come with accordance of work [34] where 0.1% SDS treatment appeared the most efficient. While a single agent decellularization with 2% SDS was found more efficient among the range of concentrations [35] it was suggested that two reagents might exhibit better decellularization with preservation of the natural tissue structure than single reagent [36].…”
supporting
confidence: 85%
“…SDS is typically more effective for removing cell residues from tissue compared to other detergents but is also more disruptive to ECM in higher concentrations and exposure time [32]. Thorough residual chemicals removal from ECM after decellularization, particularly detergents such as SDS is important as cytotoxicity is possible and will inhibit or completely negate the beneficial properties of a cell-free ECM scaffold [32,33] Our results come with accordance of work [34] where 0.1% SDS treatment appeared the most efficient. While a single agent decellularization with 2% SDS was found more efficient among the range of concentrations [35] it was suggested that two reagents might exhibit better decellularization with preservation of the natural tissue structure than single reagent [36].…”
supporting
confidence: 85%
“…The balance between cell removal and ECM preservation, efficient recellularization with new cells of dECM for obtaining homogenous cell distribution are to be optimized to use for bioprinting applications 72‐75 . These concerns include notable scaffold elicited immunogenicity due to the presence of extraneous proteins and sugars, and toxicity due to decellularization chemicals are to be addressed 76‐81 …”
Section: Bioinksmentioning
confidence: 99%
“…Studies were performed in contrast mode using the MS 250 linear transducer (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) MHz; Fujifilm VisualSonics, Inc.). Before contrast enhancement ultrasound (CEUS) imaging, the tail vein was catheterized using a 27-gauge and a PE 20 tubing (2Biological Instruments, Italia).…”
Section: Contrast Enhancement Ultrasoundmentioning
confidence: 99%